The influence of motivation, education and training, and compensation on employee performance at the representative office of Bank Indonesia in Banten Province - Dimas Ardianto Dwi Sambodo; Sunarso Sunarso; Ratu Linda Nurhasanah; John Chaidir; Haerofiatna Haerofiatna (Enrichment : Journal of Management, 2026)
This study examines the effects of motivation, education and training, and compensation on employee performance at the Representative Office of Bank Indonesia in Banten Province. It is grounded in the view that effective human resource management is crucial for sustaining organizational performance in a strategic state financial institution responsible for maintaining economic stability. Employee performance is treated as a key organizational asset influenced by internal factors such as work motivation, competency development through education and training, and the applied compensation system. Using a quantitative explanatory approach with a causal-comparative design, data were collected through questionnaires from employees who met specific criteria, including participation in training programs and receipt of formal compensation. Multiple linear regression analysis, supported by classical assumption testing, was employed to ensure model validity. Motivation, education and training, and compensation were analyzed as independent variables, while employee performance was measured through individual performance indicators, work competence, and adherence to Bank Indonesia’s strategic values. The results show that all three variables have a positive and significant effect on employee performance, both individually and collectively. The study highlights the importance of integrated motivation enhancement, continuous competency development, and fair compensation systems, contributing to public-sector human resource management literature and offering practical guidance for performance-oriented policy formulation